THE EFFECT OF TAX KNOWLEDGE, TAXATION SYSTEM MODERNIZATIONON MSME TAXPAYER COMPLIANCE IN BANDUNG CITY - Mardini, Riyang (UPT Publikasi Ilmiah UNISBA, 2024)
One of the main challenges for the government in managing state finances today is the low state revenue from the tax sector. This study aims to develop a conceptual framework of tax knowledge and modernization of the taxation system that can be used to analyze and discuss it as a factor that affects tax compliance. This study uses a purposive sampling technique based on the population of MSMEs in the food and beverage sector in Bandung, Indonesia. The analytical method used is multiple linear regression with SPSS 24. The results show that knowledge of taxation and modernization of the taxation system has a significant effect either, partially or simultaneously. Keywords : Knowledge of taxation, Modernization of the taxation system, taxpayer compliance.